Pluricentrismo, políticas académicas y los discursos sobre la lengua en la cultura lingüística hispánica - Sita Farias, Virginia (El Colegio de México, 2024)
The purpose of this paper is threefold. First, we will examine the problems related to the concept of pluricentrism, as well as the issues concerning the notion of Spanish as a pluricentric language. Secondly, we will discuss the relationship between the unity of the language and pluricentrism in pan-Hispanic language policy; in so doing, we will take into account the RAE’s discourses on standardisation. Lastly, we will analyze how the conceptualization of unity and pan-Hispanism in the academic context is reflected in the configuration of the pan-Hispanic norm and the way it is presented and addressed by the RAE.